Biodeteriorasi Semilaboratoris Daun dan Ranting Mangium dengan Aktivator Jamur Saprofitik (Semi-Laboratory Scale Biodeterioration of Mangium Leaves and Twigs with Saprophytic Fungal Activators) - Djarwanto Djarwanto; Sihati Suprapti (Jurnal Ilmu dan Teknologi Kayu Tropis, 2017)
Logging operation of mangium (Acacia mangium)’s forest generates enormous amount of wastes, such as cut-wood pieces, wood barks, twigs, and leaves.  The wastes, mainly twigs and leaves are left unutilized on logging sites.  Biodeterioration of these wastes is slow and therefore disturb local nutrient cycle.  In the present researches,  biodeterioration of mangium’s twigs and leaves were accelerated by the use of eight (8) saprophytic rotting-fungi activators.  Biodeterioration was assessed using organic-carbon content, total-nitrogen content, nutrient content, and cation-exchange capacity (CEC).  It was found that the C/N ratio after 30 and 90 days fungal inoculation decreased to 23-32 and 16-23, respectively.  C/N-ratios of lower than 20 were achieved by the use of Pycnoporus sanguineus (isolate HHBI-317), Marasmius sp, Polyporus sp., and Schizophyllum commune innoculated for 90 days.  Inoculation both for 30 and 90 days increased CEC value to >27 me per 100 g.  The high CEC value increased their adsorption capacity, storage capacity, and nutrient availability needed for plant growth.Keywords: Acacia mangium, biodeterioration, eight activator fungal species, inoculan, logging wastes, nutrient content.